Issues in discussing about family planning - Karishma Karim Halani (International Journal on Women Empowerment, 2015)
This paper highlights the concept of family planning and issues a healthcare provider faces. Further, it will discuss the causes that are responsible for it such as cultural constraints, lacking theoretical knowledge, low self-confidence and fear of non-acceptance from society. Along with this, to cater all these causes and hurdles, practical recommendations are shared to reduce this problem including self-awareness about own culture, keeping family focused approach, being master-rapport builders etc. Research journals from 2007-2012 were chosen and considered to discover reliable and divergent analysis. Family values, self-awareness and family planning are the topics that were preferred to read. These topics will come across throughout this literature review. It was clearly understood that family planning holds great importance for having a holistic health approach. It is vital to have self-awareness and knowledge about societal values on family planning to cater issues arising in this arena. This attempt will assist in rising public knowledge. It will also endorse efficient care to women and eventually the whole family. Concluding that, sensitive topics are always hidden matter in most of the cultures but the concerns attached to it cannot be ignored. Thus, it’s the basic responsibility of a nurse and other health care providers to cater these concerns through better communication skills, good rapport building, latest theoretical knowledge etc.